Radiosondes Show That After Decades of Cooling, the Lower Stratosphere Is Now Warming. Issue 22 (19th November 2018) - Philipona, Rolf; Mears, Carl; Fujiwara, Masatomo; Jeannet, Pierre; Thorne, Peter; Bodeker, Greg; Haimberger, Leopold; Hervo, Maxime; Popp, Christoph; Romanens, Gonzague; Steinbrecht, Wolfgang; Stübi, Rene; et al.
Abstract: Since the mid‐twentieth century, radiosonde and satellite measurements show that the troposphere has warmed and the stratosphere has cooled. These changes are primarily due to increasing concentrations of well‐mixed greenhouse gases and the depletion of stratospheric ozone. In response to continued greenhouse gas increases and stratospheric ozone depletion, climate models project continued tropospheric warming and stratospheric cooling over the coming decades. Global average satellite observations of lower stratospheric temperatures exhibit no significant trends since the turn of the century. In contrast, an analysis of vertically resolved radiosonde measurements from 60 stations shows an increase of lower stratospheric temperature since the turn of the century at altitudes between 15 and 30 km and over most continents. Trend estimates are somewhat sensitive to homogeneity assessment choices, but all investigated radiosonde data sets suggest a change from late twentieth century cooling to early 21st century warming in the lower stratosphere, which is consistent with a reversal from ozone depletion to recovery from the effects of ozone‐depleting substances. In comparison, satellite observations at the radiosonde locations show only minor early 21st century warming, possibly due to the compensating effects of continued cooling above the radiosonde altitude range. Key Points: Radiosonde profiles show that after decades of cooling, the lower stratosphere is now warming Over all continents radiosonde measured TLS trends since 2000 are larger than satellite‐observed trends